Respiratory infections in yak (Bos grunniens): a pilot study on isolation and direct PCR diagnosis for pasteurellosis, mannheimiosis and histophilosis - SAHAY, SWATI; JAYARAM, POOJA K P; NATESAN, KRITHIGA; DOLEY, JUWAR; REDDY, G B MANJUNATHA; PATIL, SHARAN S; SHOME, BIBEK RANJAN; SHOME, RAJESWARI (The Indian Journal of Animal Sciences, 2018)
Bovine respiratory disease (BRD) is a condition of severe pneumonia caused due to environmental stress followed by a multiple viral and bacterial pathogens.The present study aimed to detect the BRD agents such as Mannhaeimia haemolytica, Pasteurella multocida and Histophilus somni and IBR in yaks suffering from respiratory infections. For the study, 157 deep nasal and blood samples were collected from yak of Arunachal Pradesh and processed for isolation and PCR detection of respiratory bacterial pathogens such as M. haemolytica, P. multocida and H. somni and seroscreening of IBR. From 157 samples, one M. haemolytica and two H. somni isolates were recovered. This is the first report of H. somni and M. haemolytica isolation from yak nasal samples from India. In mPCR, 23 yak nasal samples (14.6%) amplified for M. haemolytica, two (1.2%) for P. multocida and six samples for H. somni (4.6%) by simplex PCR. Concurrence of H. somni and M. haemolytica in three samples, and M. haemolytica and P. multocida type B in two samples was also observed.Very high seroprevalence for IBR (37%) by Indirect ABELISA was recorded.The study concluded that highest number of samples were positive for M. haemolytica (14.6%) and emphasizes its role in respiratory infections along with high seroprevalence of IBR. It also reflected the diagnostic importance of mPCR/PCR in regions inaccessible for fresh sample collection and transportation as an alternate to isolation procedures.